Promoting quality and productivity in bureaucratic/administrative performance in Malaysia - Rahman, Abdullah Bin Abdul (Asian Review of Public Administration, 1991)
Planning and implementing quality and productivity improvement programmes involve managing change. In this respect, management commitment is vital and critical. This management commitment must be reflected in various ways including the formulation of a quality policy and the allocation of the necessary resources. Also the system within an organization must be supportive of change. These systems include the motivational subsystem, monitoring and evaluation subsystem and the training subsystem to facilitate the change process. Only through providing the right motivation, inculcating positive attitudes and the transfer of the relevant knowledge and skills can changes be made.